Palgrave Advances in Modern Military History - Hughes, Matthew. (Palgrave Advances, 2006)
This book provides a concise and accessible introduction to modern military history. The collection is a clear and up to date survey of the significant debates, interpretations and historiographical shifts for a series of key themes in military history. Each chapter is supported by notes and a brief bibliography outlining further reading.